Crescimento, composição mineral e sintomas visuais de deficiência nutricional em ipeca - Viegas, Ismael De Jesus Matos; Rodrigues Galvão, Jessivaldo; Da Silva Jr., Mário Lopes; Carvalho Melo, Nilvan [UNESP]; De Oliveira, Miriam Sarmento (My University, 2014)
The objective was to evaluate the effect of the omission of macronutrient and micronutrient boron in dry matter production, the characterization of the symptoms of nutritional deficiencies and mineral composition in plants of ipeca, an experiment was conducted in greenhouse conditions by the technique the missing element and visual diagnosis. A randomized block experimental design with four repetitions and the treatments were: complete and omissions of N, P, K, Ca, Mg, S and B. The analytical results demonstrated that the production of dry matter was affected in all of the treatments with omission of nutrients and that the ipeca plants presented characteristic symptoms of nutritional deficiencies due to the omissions of N, P, K, Ca, Mg, S and B and the concentrations of the macronutrients and of the micronutrient boron in the different parts of the ipeca plant varied when a certain nutrient was omitted in the solution.
Growth, mineral composition and symptoms of visual impairment in nutrition ipeca
Keywords: Levels of nutrients; Mineral nutrition; Production of dry matter; Psychotria ipecacuanha